Protocol for an economic evaluation of WHO STOPS childhood obesity stepped-wedge cluster randomised controlled trial. Issue 5 (14th May 2018) - Sweeney, Rohan; Moodie, Marj; Nguyen, Phuong; Fraser, Penny; Bolton, Kristy; Brown, Andrew; Marks, Jennifer; Crooks, Nic; Strugnell, Claudia; Bell, Colin; Millar, Lynne; Orellana, Liliana; et al.
Abstract : Introduction: Prevention of overweight and obesity in childhood is a priority because of associated acute and chronic conditions in childhood and later in life, which place significant burden on health systems. Evidence suggests prevention should engage a range of actions and actors and target multiple levels. The Whole of Systems Trial Of Prevention S trategies for childhood obesity (WHO STOPS) will evaluate the outcomes of a novel systems-based intervention that aims to engage whole communities in a locally led multifaceted response. This paper describes the planned economic evaluation of WHO STOPS and examines the methodological challenges for economic evaluation of a complex systems-based intervention. Methods and analysis: Economic evaluation alongside a stepped-wedge cluster randomised controlled trial in regional and rural communities in Victoria, Australia. Cost-effectiveness and cost–utility analyses will provide estimates of the incremental cost (in $A) per body mass index unit saved and quality adjusted life year gained. A Markov cohort model will be employed to estimate healthcare cost savings and benefits over the life course of children. The dollar value of community resources harnessed for the community-led response will be estimated. Probabilistic uncertainty analyses will be undertaken to test sensitivity of results to plausible variations in all trial-based and modelled variables. WHO STOPS will also be assessed against other implementation considerations (such as sustainability and acceptability to communities and other stakeholders). Ethics and dissemination: The trial is registered by the Australian New Zealand Clinical Trials Registry (ACTRN12616000980437). Full ethics clearances have been received for all methods described below: Deakin University's Human Research Ethics Committee 2014-279, Deakin University's Human Ethics Advisory Group-Health (HEAG-H) HEAG-H 194_2014, HEAG-H 17 2015, HEAG-H 155_2014, HEAG-H 197_2016, HEAG-H 118_2017, the Victorian Department of Education and Training 2015_002622 and the Catholic Archdiocese of Ballarat. Trial findings (including economic evaluation) will be published in peer-reviewed journals and presented at international conferences. Collected data and analyses will be made available in accordance with journal policies and study ethics approvals. Results will be presented to relevant government authorities with an interest in cost-effectiveness of these types of interventions. Trial registration number: ACTRN12616000980437; Pre-results.